Surface processes and drivers of the snow water stable isotopic composition at Dome C, East Antarctica – a multi-dataset and modelling analysis - Ollivier, Inès; Steen-Larsen, Hans Christian; Stenni, Barbara; Arnaud, Laurent; Casado, Mathieu; Cauquoin, Alexandre; Dreossi, Giuliano; Genthon, Christophe; Minster, Bénédicte; Picard, Ghislain; Werner, Martin; Landais, Amaëlle (The Cryosphere, 2025)
Water stable isotope records in polar ice cores have been largely used to reconstruct past local temperatures and other climatic information such as evaporative source region conditions of the precipitation reaching the ice core sites. However, recent studies have identified post-depositional processes taking place at the ice sheet's surface, modifying the original precipitation signal and challenging the traditional interpretation of ice core isotopic records. In this study, we use a combination of existing and new datasets of precipitation, snow surface, and subsurface isotopic compositions (delta 18O and deuterium excess (d-excess)); meteorological parameters; ERA5 reanalyses; outputs from the isotope-enabled climate model ECHAM6-wiso; and a simple modelling approach to investigate the transfer function of water stable isotopes from precipitation to the snow surface and subsurface at Dome C in East Antarctica. We first show that water vapour fluxes at the surface of the ice sheet result in a net annual sublimation of snow, from 3.1 to 3.7 mm w.e. yr-1 (water equivalent) between 2018 and 2020, corresponding to 12 % to 15 % of the annual surface mass balance. We find that the precipitation isotopic signal cannot fully explain the mean, nor the variability in the isotopic composition observed in the snow, from annual to intra-monthly timescales. We observe that the mean effect of post-depositional processes over the study period enriches the snow surface in delta 18O by 3.0 parts per thousand to 3.3 parts per thousand and lowers the snow surface d-excess by 3.4 parts per thousand to 3.5 parts per thousand compared to the incoming precipitation isotopic signal. We also show that the mean isotopic composition of the snow subsurface is not statistically different from that of the snow surface, indicating the preservation of the mean isotopic composition of the snow surface in the top centimetres of the snowpack. This study confirms previous findings about the complex interpretation of the water stable isotopic ...